Brazil : How Do the Peri-urban Poor Meet their Energy Needs - A Case Study of Caju Shantytown, Rio de Janeiro - World Bank (Washington, DC, 2014)
The phenomenon of poverty has traditionally been measured based on the individual's income. However, more recently, the debate over poverty has evolved beyond income or lack of it. The condition in which people have access to basic civil rights, such as an adequate energy supply, is nowadays considered an important marker of poverty. This study proposes to analyze energy poverty in the shantytowns of Rio de Janeiro. The authors aim is to suggest public policies that can, with support from electric utilities, contribute to improving the living conditions of the shantytown inhabitants. The study was carried out using both quantitative and qualitative data.